Az oktatás megindulásának 100 év előtti emlékei - Virágos, Márta (Gerundium, 2014)
SCHOOL YEAR OPENING IN 1914. he irst oicial school year opening of the Hungarian Royal University of Debrecen was organized on October 1, 1914 in the Great Church. he event was reported by several newspaper of the time. he detail history of the establishment of the Universiy of Debrecen was irst written by dr. Béla Kun (later known as Béla Szentpéteri Kun) in the Almanach of the Hungarian Royal University of Debrecen in 1914, and published in printed format only in 1916. he third chapter of the essay is available in full text.